SAT0698-HPR SYSTEMATIC LITERATURE REVIEW AND META-ANALYSIS OF INFECTION TYPES AND THE EFFECT OF MEDICATIONS ON INFECTION IN SYSTEMIC LUPUS ERYTHEMATOSUS. (June 2019) - Barroso, Nashla S.; Aly, Aly M.; Zaccagnino, Ethan; Wendy, LI; Agrawal, Harsh; Doaty, Sarah M.; Furst, Daniel
Abstract : Background: The infection incidence rates are high in systemic lupus erythematosus (SLE) patients 1 and the medical literature documents broad categories of specific bacterial infection risks for SLE patients. 2-4 However, there has not been a detailed incidence of infection types and infection predictors. Objectives: In a systemic literature review (SLR) and meta-analysis, to describe the types and incidences of infections in SLE patients and to examine the effect of medications used to treat SLE. Methods: An SLR of SLE and infection articles generated through a search of MeSH terms using PubMed and Medline generated 1, 211 articles. Using predefined Incl/Exc criteria, data from 32 accepted articles were double-extracted and descriptive and multivariable analyses were conducted. Relative risks between drug classes were estimated using Arm-Based Network Meta-Analysis. Hypothesis tests were two-sided and a p-value <0.05 was statistically significant. Analysis was conducted in the R Statistical Computing Environment (R Core Team; Vienna, Austria). Results: 4, 130 patients were considered, 91% females, average age: 36.8 (10.9) years, mean disease duration: 6.9 (6.1) years, SLEDAI mean: 11.7 (4.6). In drug trials, 775 used conventional synthetic DMARDs (csDMARDs), 1, 809 (43.8%) used biologic DMARDs (bDMARDs), 691 (16.7%) used placebo and the rest were in non-drug specific observational studies. 90.4% used background corticosteroid therapy. Bacterial infections occurred most commonly, being 61% of the total of 315 non-serious infections, of which 28.4% were gram negative and 15.3% gram positive. 135 (42.9%) had viral infection – H zoster, HPV, and CMV were most common. 36 (11.4%) were opportunistic infections - 12 candida, 11 mycobacterial, 4 pneumocystis jiroveci pneumonia, and 9 unspecified infections. There were 182 serious infections (SIE), of which 110 were bacterial (gram negative were the most common subtype (36.3%)). Serious opportunistic infections accounted for 31 (17%) of the SIEs, similar to serious viral infections 41 (22.5%). Patients using csDMARDs had an absolute risk to develop H Zoster of 15.2% (95% CI: 7.7-28.2), while it was 8.2% (CI: 1.9-29.2%) when using bDMARDs. The next most likely infection for which these SLE patients were at risk was for gram negative infections, where csDMARDs demonstrated a 7% absolute risk (CI: 0.4-36%) of developing a gram negative infection, compared to 5.6% (CI: 0.1-52.6%) for bDMARDs. The attributable risk for developing gram positive infections when using csDMARDs was 3.9% (CI: 0.2-25%) and 3.5% (CI: 0.1-41.6%) when using bDMARDs. Conclusion: In this SLR and meta-analysis in SLE, the frequency of infections was bacterial>viral > opportunistic, in that order, although some details were unavailable. csDMARDs were associated with more infections than bDMARDs. References: [1] Ramos M, Cuadrado MJ, Abla P, et al. (2008) Acute viral infections in patients with SLE: description of 23 cases and review of the literature. Medicine (Baltimore) 87:311-318. [2] Feldman, et al. (2015) Serious infections among adult Medicaid beneficiaries with SLE and lupus nephritis. Arthritis Rheumatol 67: 1577-1585. [3] Dubula T, Mody GM (2015) Spectrum of infections and outcome among hospitalized South Africans with SLE. Clin Rheumatol 34: 479-488. [4] Bouza E, Moya JG, Muñoz P (2001) Infections in SLE and RA. Infect Dis Clin North Am 15: 335-361. Acknowledgement: J. Grotts Disclosure of Interests: Nashla S Barroso: None declared, Aly M Aly: None declared, Ethan Zaccagnino: None declared, Wendy Li: None declared, Harsh Agrawal: None declared, Sarah M Doaty: None declared, Daniel Furst Grant/research support from: F. Hoffmann-La Roche, Genentech